The role of NFKB1 and NFKBIA in immunoglobulin A vasculitis - Batista-Liz, Joao Carlos; Sebastián Mora-Gil, María; Renuncio García, Mónica; Leonardo, María Teresa; Peñalba, Ana; Gabrie, Ligia; Sánchez, Rafael Gálvez; Martín-Penagos, Luis; Narvaez, Javier; Sevilla-Pérez, Belén; Ríos Fernández, Raquel; Callejas-Rubio, José Luis; et al. (Frontiers in Immunology, 2025)
IntroductionImmunoglobulin A vasculitis (IgAV) is an inflammatory disease mediated by B cells. Nuclear factor kappa B (NF-κB) is essential for B-cell development and maturation and plays a key role in autoimmunity and inflammation. In particular, the NF-κB canonical activation pathway genes NFKB1 (encoding NF-κB1) and NFKBIA (encoding NF-κB inhibitor alpha) have been identified as risk loci for several immune-mediated diseases, but their role in IgAV remains unclear. This study aimed to determine whether NFKB1 and NFKBIA represent novel genetic risk factors for IgAV pathogenesis.MethodsThe NFKB1 promoter variant −94 ins/del ATTG (rs28362491), six tag NFKB1 polymorphisms (rs77830930, rs1598856, rs7340881, rs4648055, rs4648090, and rs230547), and seven tag NFKBIA variants (rs3138055, rs696, rs1022714, rs2233419, rs2233415, rs1050851, and rs1957106) were genotyped in 343 Caucasian IgAV patients and 764 healthy, ethnically matched controls using TaqMan probes. Patients were stratified according to age at disease onset and the presence or absence of renal, articular, and gastrointestinal manifestations. Genotype, allele, and haplotype frequencies were compared between patients and controls, as well as across clinical subgroups.ResultsNo statistically significant differences were found in genotype or allele frequencies of NFKB1 or NFKBIA between IgAV patients and healthy controls. Likewise, haplotype frequencies of both genes were similar across groups. No associations were observed when patients were stratified by clinical features, including renal involvement, age at onset, or articular/gastrointestinal symptoms.ConclusionOur findings do not support a major role for the NFKB1 or NFKBIA variants studied in IgAV susceptibility or severity. These results suggest that if NF-κB signaling contributes to IgAV pathogenesis, it likely involves other biological mechanisms.